Bentuk Implementasi P2TL (Peraturan Pencegahan Tubrukan di Laut) guna Mencegah Terjadinya Kecelakaan Kapal di Laut dalam Rangka Mendukung Perekonomian Negara - Albertus Mario Ari Setyawan; Aartje Tehupeiori; Wiwik Sri Widiarty (Syntax Idea)
This research explores the implementation of the COLREG (Convention on the International Regulations for Preventing Collisions at Sea 1972) in efforts to prevent ship accidents in Indonesian waters, with the aim of supporting the country's economic growth. COLREG, referring to the Convention on the International Regulations for Preventing Collisions at Sea 1972, is a set of international rules governing ship navigation in global open waters. These rules are established by the International Maritime Organization (IMO) and focus on regulating ship navigation to prevent collisions at sea. Ship collision accidents have serious impacts, including risks to human life, property damage, and environmental consequences. The causes of these accidents can vary and may include human error, equipment malfunction, procedural violations, rule violations, external actions, and natural factors. The implementation of COLREG in Indonesia is essential for reducing collision incidents, especially those caused by human error. Although COLREG has not received official ratification, its implementation based on Presidential Decree No. 50 of 1979 serves as guidance followed by ships in Indonesia. Adherence to COLREG rules enhances navigation safety, ultimately contributing to economic growth through the maritime sector.